An experimental study on flexural strength of reinforced concrete beams with 100% recycled concrete aggregate. (1st April 2015) - Arezoumandi, Mahdi; Smith, Adam; Volz, Jeffery S.; Khayat, Kamal H.
Highlights: Existing design codes can be used for flexural design of the HVFAC beams. The HVFAC beams showed lower deflection compared with the CC beams. In general, the HVFAC beams flexural strengths exceeded the code predicted values. Abstract: The following paper presents the results of an experimental investigation of the flexural strength of full-scale reinforced concrete beams constructed with both 100% recycled concrete aggregate (RCA) as well as conventional concrete (CC). This experimental program consisted of eight beams (four for each concrete type). The test parameters for this study include longitudinal reinforcement ratio and concrete type. The beams were tested under a simply supported four-point loading condition. The experimental cracking, yielding, and ultimate moment of the beams were compared with the ACI 318-11 and Eurocode 2-05 provisions and the modified compression field theory (MCFT) method. Furthermore, the experimental flexural strengths of the beams were compared with both flexural test databases of CC and RCA specimens. Results of this study show that the RCA beams have comparable ultimate flexural strength and approximately 13% higher deflection corresponding to the ultimate flexural strength of the CC beams.